Double‐Hydrophobic‐Coating through Quenching for Hydrogels with Strong Resistance to Both Drying and Swelling. Issue 6 (24th January 2020) - Mredha, Md. Tariful Islam; Le, Hong Hieu; Cui, Jiaxi; Jeon, Insu
Abstract: In recent years, various hydrogels with a wide range of functionalities have been developed. However, owing to the two major drawbacks of hydrogels—air‐drying and water‐swelling—hydrogels developed thus far have yet to achieve most of their potential applications. Herein, a bioinspired, facile, and versatile method for fabricating hydrogels with high stability in both air and water is reported. This method includes the creation of a bioinspired homogeneous fusion layer of a hydrophobic polymer and oil in the outermost surface layer of the hydrogel via a double‐hydrophobic‐coating produced through quenching. As a proof‐of‐concept, this method is applied to a polyacrylamide hydrogel without compromising its mechanical properties. The coated hydrogel exhibits strong resistance to both drying in air and swelling in multiple aqueous environments. Furthermore, the versatility of this method is demonstrated using different types of hydrogels and oils. Because this method is easy to apply and is not dependent on hydrogel surface chemistry, it can significantly broaden the scope of next‐generation hydrogels for real‐world applications in both wet and dry environments. Abstract : A double‐hydrophobic‐coating method using a hydrophobic polymer and a viscous oil prepared via quenching is developed to fabricate hydrogels with strong resistance to drying in air and swelling in multiple aqueous environments. The method is not dependent on the type of oil or the surface chemistry of the hydrogel used; therefore, it is applicable to a wide range of hydrogels.